2022
DOI: 10.5535/arm.21127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paraplegia Fitness Integrated Training on Physical Function and Exercise Self-Efficacy and Adherence Among Individuals With Spinal Cord Injury

Abstract: Objective To determine the effects of the Paraplegia Fitness Integrated Training (PARAFiT) program, which is an integrated graded physical exercise and health education program for individuals with spinal cord injury (SCI).Methods This nonrandomized single-blind study included 44 participants, who were assigned to either an intervention (PARAFiT) group or an active control (conventional physiotherapy) group. The intervention group underwent the PARAFiT program (8 weeks), which consisted of circuit-based interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As warm-up trials decrease the variability of strength measurements [ 54 ], participants will be given 1 warm-up trial for each hand. A total of 3 attempts will be made for each hand for a duration of 3 seconds each at a 90-degrees elbow flexion and neutral wrist position [ 54 , 55 , 57 ]. A rest period of 60 seconds will be provided in between.…”
Section: Methodsmentioning
confidence: 99%
“…As warm-up trials decrease the variability of strength measurements [ 54 ], participants will be given 1 warm-up trial for each hand. A total of 3 attempts will be made for each hand for a duration of 3 seconds each at a 90-degrees elbow flexion and neutral wrist position [ 54 , 55 , 57 ]. A rest period of 60 seconds will be provided in between.…”
Section: Methodsmentioning
confidence: 99%
“…To identify problems associated with physical activity in adults with SCI, a prospectively registered systematic review assessed the effectiveness of behaviour change interventions in this context (32). In addition, the literature regarding the barriers and facilitators to physical activity in this population was also reviewed (79,80). This information was used to define the problem as: how to improve physical activity in adults with SCI to meet recommended guidelines (at least 20 minutes of moderate to vigorous intensity-aerobic activity alongside strength training exercises twice per week) leading to reduced sedentary behaviours (Table S1).…”
Section: Step 1: Define the Problem In Behavioural Termsmentioning
confidence: 99%
“…The results of these studies were based on various qualitative and mix-method studies that relied on more self-reported experiences and perceptions of persons with SCI. However, these studies have limitations; they do not reveal the type, frequency, or duration of particular activities of daily living participation inside and outside the home, nor do they specifically address the impact of various obstacles and facilitators factors to participation in daily activities such as individualised factors, gender, education, interest, mastery in activities, residence in higher, middle and lower income countries, community level supports, social support system and wealth (16,17,18,19). Moreover, several existing studies have explored the internal and external factors affecting the resumption of daily activities for persons with SCI during their transition from hospital facilities to the community, they tend to primarily focus on the individual's physical aspects and environmental challenges.…”
Section: Introductionmentioning
confidence: 99%